2017
DOI: 10.1061/(asce)wr.1943-5452.0000854
|View full text |Cite
|
Sign up to set email alerts
|

Scenario-Tree Modeling for Stochastic Short-Term Hydropower Operations Planning

Abstract: The authors investigate the complexity needed in the structure of the scenario trees to maximize energy production in a rolling-horizon framework. Three comparisons, applied to the stochastic short-term unit commitment and loading problem are conducted. The first one involves generating a set of scenario trees built from inflow forecast data over a rolling-horizon. The second replaces the entire set of scenario trees by the median scenario. The third replaces the set of trees by scenario fans. The method used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…2), rather than a scenario tree (with a limited number of nodes for approximating the stochastic inflows). In numerical experiments on short-term hydropower planning using a scenario fan formulation with decisions updated in a rolling horizon, Séguin et al (2017a) achieved comparable solutions to those obtained from a scenario tree model, while requiring less computational effort. Although the performance of the scenario fan and the scenario tree models depend on multiple factors, such as the specific problem, its formulation and the implemented solution method, the empirical results in Séguin et al (2017a) suggest that a scenario fan approach may be promising in some practical applications where computational times are critical.…”
Section: Modeling Approachmentioning
confidence: 93%
“…2), rather than a scenario tree (with a limited number of nodes for approximating the stochastic inflows). In numerical experiments on short-term hydropower planning using a scenario fan formulation with decisions updated in a rolling horizon, Séguin et al (2017a) achieved comparable solutions to those obtained from a scenario tree model, while requiring less computational effort. Although the performance of the scenario fan and the scenario tree models depend on multiple factors, such as the specific problem, its formulation and the implemented solution method, the empirical results in Séguin et al (2017a) suggest that a scenario fan approach may be promising in some practical applications where computational times are critical.…”
Section: Modeling Approachmentioning
confidence: 93%
“…As reliable SF observations are not available in data-scarce regions to validate the reservoir inflow forecasts, the assumption of a deterministic first stage may not be appropriate. For example, Séguin et al (2017) highlight the importance of stochastic scenarios on hydropower by comparing scenario trees of varying complexities: (1) full scenario tree with SPWR-D, (2) scenario tree with only the median scenario at all stages, and (3) scenario fan. They conclude that, for hydropower planning, stochastic scenarios (scenario tree or fans) are preferable over deterministic scenarios.…”
Section: Formulation Of the Hydropower Optimization Modelmentioning
confidence: 99%
“…They conclude that, for hydropower planning, stochastic scenarios (scenario tree or fans) are preferable over deterministic scenarios. In this study, we extend the comparisons presented in Séguin et al (2017) by reformulating the stochastic programming with recourse model for hydropower planning to consider the uncertainty in seasonal reservoir inflow forecasts at the first/immediate stage. Specifically, we evaluate the impact of considering deterministic and stochastic first stages in reservoir inflows on the optimized released decisions and hence hydropower production.…”
Section: Formulation Of the Hydropower Optimization Modelmentioning
confidence: 99%
“…The method has been used previously, (e.g. in Shukla andLettenmaier, 2011 andGreuell et al, 2018) where the pseudo-observations are shown to be the best estimate of the true conditions of the catchment. The ESP forecasts were generated following a straightforward procedure:…”
Section: Preparation Of Esp Forecastsmentioning
confidence: 99%